The Provision of Visitable Housing in Australia: Down to the Detail - Ward, Margaret (Social Inclusion, 2015)
In response to the ratification of the United Nations Convention of the Rights of People with Disabilities (CRPD), Australian housing industry leaders, supported by the Australian Government, committed to transform their practices voluntarily through the adoption of a national guideline, called Livable Housing Design. They set a target in 2010 that all new housing would be visitable by 2020. Research in this area suggests that the anticipated voluntary transformation is unrealistic and that mandatory regulation will be necessary for any lasting transformation to occur. It also suggests that the assumptions underpinning the Livable Housing Design agreement are unfounded. This paper reports on a study that problematised these assumptions. The study used eleven newly-constructed dwellings in three housing contexts in Brisbane, Australia. It sought to understand the logics-of-practice in providing, and not providing, visitable housing. By examining the specific details that make a dwelling visitable, and interpreting the accounts of builders, designers and developers, the study identified three logics-of-practice which challenged the assumptions underpinning the Livable Housing Design agreement: focus on the point of sale; an aversion to change and deference to external regulators on matters of social inclusion. These were evident in all housing contexts indicating a dominant industry culture regardless of housing context or policy intention. The paper suggests that financial incentives for both the builder and the buyer, demonstration by industry leaders and, ultimately, national regulation is a possible pathway for the Livable Housing Design agreement to reach the 2020 goal. The paper concludes that the Australian Government has three options: to ignore its obligations under the CRPD; to revisit the Livable Housing Design agreement in the hope that it works; or to regulate the housing industry through the National Construction Code to ensure the 2020 target is reached.